PEMANFAATAN LINGKUNGAN RUMAH MELALUI PELATIHAN PEMBUATAN BIOPORI DI KELURAHAN PURWOYOSO KECAMATAN NGALIYAN KOTA SEMARANG - Nuryanti; Zusrotin; Eko Heri Widiastuti; R.Soelistijanto (Jurnal Pengabdian Masyarakat Waradin, 2021)
Community service with counseling steps carried out by the Extension Team of the Department of History Education, Faculty of Teacher Training and Education, Ivet University in Purwoyoso Village, Ngaliyan District, Semarang City, has succeeded in increasing public awareness of the importance of a healthy environment and making absorption through Biopori. Human life, cannot be separated from the environment around the house where you live. Both the natural environment and the social environment. We breathe requires air from the environment. Eating, drinking, keeping healthy, everything involves the environment. From the environment, humans can take advantage of parts of the environment such as animals, plants, water, air, sunlight, salt, wood, mining products and so on for their daily needs. But it is not only humans who live like that. Other living things such as animals and microbial animals and plants can also live because of their environment. A healthy environment in the form of shady plants and trees can be a source of oxygen and become a shelter for residents. Apart from being a shelter for residents, it is also a place for residents to chat and play with children. The role of Biopores is also important, as water infiltration when it rains so that it can provide water for the plants around it, so that the plants around it become fertile.